Are health care workers following preventive practices in the COVID-19 pandemic properly? - A cross-sectional survey from India. Issue 1 (January 2021) - Agarwal, Ayush; Ranjan, Piyush; Saraswat, Arjun; Kasi, Keerthana; Bharadiya, Vishwesh; Vikram, Naval; Singh, Amandeep; Upadhyay, Ashish Datt; Baitha, Upendra; Klanidhi, Kamal Bandhu; Chakrawarty, Avinash
Abstract: Background and aims: Health care workers (HCWs) are at increased risk of getting infected with Coronavirus disease 2019 (COVID-19) and suboptimal preventive practices have been identified as an important risk factor in this regard. This study was done to evaluate the preventive practices being followed by health care workers and identify reasons for suboptimal compliance. Methods: A cross-sectional survey was done in HCWs belonging to various occupational roles and socio-cultural backgrounds across India through online platforms and telephonic interviews from July 30, 2020 to August 30, 2020. A scientifically designed and pre-validated questionnaire with good validity (CVR = 0.87, S-CVI/Av = 0.978) and internal consistency (Cronbach's alpha coefficient = 0.85) was used. Results: The responses of 956 participants were analysed. Various suboptimal practices like touching outer surface of masks, lack of social distancing in cafeteria and duty rooms, inability to wash hands for adequate duration and properly follow steps of hand hygiene, inability to don and doff PPE properly, carrying PPE to duty rooms before completely doffing, use of personal mobile phones during duty and improper sleep were identified. Lack of knowledge, long duty hours, shortage of PPE, high patient workload, and casual attitude regarding own safety were identified as important barriers. Resident doctors and paramedical staff in the age group 18–30 years reported lower adherence. Conclusions: Suboptimal compliance in preventive practices like handling PPE, distancing in cafeteria/duty rooms and hand hygiene is not uncommon in HCWs. Certain barriers are identified which should be addressed to ensure adequate safety of HCWs against COVID-19. Highlights: COVID-19 has affected millions of health care workers worldwide. Suboptimal adherence to hand hygiene, social distancing, PPE use, etc reported. Barriers include ignorance, long duty hours, shortage of PPE and high workload. Regular training, reinforcement and robust surveillance is recommended.